Morphomechanics and Developmental Constraints in the Evolution of Ammonites Shell Form. Issue 7 (6th December 2016) - Erlich, Alexander; Moulton, Derek E.; Goriely, Alain; Chirat, Regis
GRAPHICAL ABSTRACT: A mathematical model shows that the biomechanics of the shell secreting system underlies a morphogenetic rule of variation in ammonites. This rule channeled their evolution along predictable paths and constituted a developmental constraint . ABSTRACT: The idea that physical processes involved in biological development underlie morphogenetic rules and channel morphological evolution has been central to the rise of evolutionary developmental biology. Here, we explore this idea in the context of seashell morphogenesis. We show that a morphomechanical model predicts the effects of variations in shell shape on the ornamental pattern in ammonites, a now extinct group of cephalopods with external chambered shell. Our model shows that several seemingly unrelated characteristics of synchronous, ontogenetic, intraspecific, and evolutionary variations in ornamental patterns among various ammonite species may all be understood from the fact that the mechanical forces underlying the oscillatory behavior of the shell secreting system scale with the cross‐sectional curvature of the shell aperture. This simple morphogenetic rule, emerging from biophysical interactions during shell formation, introduced a non‐random component in the production of phenotypic variation and channeled the morphological evolution of ammonites over millions of years. As such, it provides a paradigm for the concept of "developmental constraints."